Evangelical Millennialism in the Trans-Atlantic World, 1500-2000 - Gribben, C.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
This book offers the first complete overview of the intellectual history of one of the most significant contemporary cultural trends – the apocalyptic expectations of European and American evangelicals – in an account that guides readers into the origins, its evolution, and its revolutionary potential in the modern world.
Keywords: World history; Civilization—History.; Religion—Philosophy.; Imperialism; Social history; Theology; World History, Global and Transnational History; Cultural History; Philosophy of Religion; Imperialism and Colonialism; Social History; Christian Theology